B20–MnSi films grown on Si(100) substrates with magnetic skyrmion signature. (November 2021) - Li, Zichao; Yuan, Ye; Hübner, René; Begeza, Viktor; Naumann, Thomas; Rebohle, Lars; Hellwig, Olav; Helm, Manfred; Nielsch, Kornelius; Prucnal, Slawomir; Zhou, Shengqiang
Abstract: Magnetic skyrmions have been suggested as information carriers for future spintronic devices. As the first material with experimentally confirmed skyrmions, B20-type MnSi was the research focus for more than a decade. Although B20–MnSi films have been successfully grown on Si(111) substrates, there is no report about B20–MnSi films on Si(100) substrates, which would be more preferred for practical applications. In this letter, we present the first preparation of B20–MnSi on Si(100) substrates. It is realized by sub-second solid-state reaction between Mn and Si via flash-lamp annealing at ambient pressure. The regrown layer shows an enhanced Curie temperature of 43 K compared with bulk B20–MnSi. The magnetic skyrmion signature is obtained in our films by magnetic and transport measurements. The millisecond-range flash-lamp annealing provides a promising avenue for the fabrication of Si-based skyrmionic devices. Graphical abstract: Image 1 Highlights: B20-type MnSi with magnetic skyrmions is fabricated for the first time on Si(100) substrates. The Curie temperature of the MnSi films is increased to around 43 K. The skyrmion stabilization is enhanced regarding both magnetic field and temperature ranges.